2008
DOI: 10.1007/978-0-387-69080-3_45
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Peptide Derived from Alpha-fetoprotein Inhibits the Estradiol-induced Proliferation of Mammary Tumor Cells in Culture through the Modulation of p21

Abstract: A stable cyclized 9-mer peptide (cP) containing the active site of alpha-alpha fetoprotein (alphaFP) has been shown to be effective for prevention of estrogen-stimulated tumor cell proliferation in culture or of xenographt growth in immunodeficient mice. cP does not block 17beta-estradiol (E2) binding to its receptors, but rather appears to interfere with intracellular processing of the signal that supports growth. To obtain insight on that mechanism we studied the effect of cP on the proliferation of MCF-7 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…AFPep does neither of these but does interfere with the phosphorylation of the ER, particularly at Ser 118 (64) but not at Ser 167 or Ser 104 (62). Unlike tamoxifen, AFPep does not alter the number of binding sites or their affinity for radiolabled estrogen (65,67,68 (67). AFPep interfered markedly with the regulation of mitogen-activated protein kinase (MAPK) by activated c-erbB2; it showed no effect on estrogen-stimulated release of matrix metalloproteinases 2 and 9 (69).…”
Section: Afpep Has a Unique Mechanism Of Actionmentioning
confidence: 96%
“…AFPep does neither of these but does interfere with the phosphorylation of the ER, particularly at Ser 118 (64) but not at Ser 167 or Ser 104 (62). Unlike tamoxifen, AFPep does not alter the number of binding sites or their affinity for radiolabled estrogen (65,67,68 (67). AFPep interfered markedly with the regulation of mitogen-activated protein kinase (MAPK) by activated c-erbB2; it showed no effect on estrogen-stimulated release of matrix metalloproteinases 2 and 9 (69).…”
Section: Afpep Has a Unique Mechanism Of Actionmentioning
confidence: 96%
“…However, GIP-8 seemed to have no effect on MMP-2, MMP-9, and heparin-binding EGF cancer cell surface shedding, all of which are prerequisites for metastasis. Following that study, Sierralta et al showed that GIP-8 had no effect on apoptosis and did not alter E-cadherin levels, but did modulate the cytosolic levels of p21 CIP which act to hinder cell cycle transition of S to G2 phase [63]. Finally, it was demonstrated that GIP-8 could be conjugated to doxorubicin (DOX) in order to improve chemotherapeutic drug delivery and increase toxicity of the chemodrug.…”
Section: The Gip-8 Segment: Properties Traits and Biological Activitiesmentioning
confidence: 99%
“…Once in the cytoplasm, GIP-8 has been demonstrated to inhibit the E-stimulated phosphorylation of serine-118 of human ER in lysates of T47D breast cancer cells; it also interferes with the phosphorylation of p53, an event that inactivates this tumor suppressor [56]. Further data provided by Sierralta et al showed that GIP-8 caused an increase in cytoplasmic P21 Cip levels, but had no effect on E-cadherin expression, apoptosis, and endogenous aromatase activity in both MCF-7 and ZR75-1 human breast cancer cells [63]. The authors of this latter report stated that GIP-8 suppressed cell cycle progression at the S to G2 phase via regulation of the p21Cip cyclin inhibitor.…”
Section: Proposed Mechanism Of Action: Gip-8/afpepmentioning
confidence: 99%